Targeting the genetic landscape of oral potentially malignant disorders has the potential as a preventative strategy in oral cancer. (10th October 2021) - Prime, S.S.; Cirillo, N.; Cheong, S.C.; Prime, M.S.; Parkinson, E.K.
Abstract: This study reviews the molecular landscape of oral potentially malignant disorders (OPMD). We examine the impact of tumour heterogeneity, the spectrum of driver mutations ( TP53, CDKN2A, TERT, NOTCH1, AJUBA, PIK3CA, CASP8 ) and gene transcription on tumour progression. We comment on how some of these mutations impact cellular senescence, field cancerization and cancer stem cells. We propose that OPMD can be monitored more closely and more dynamically through the use of liquid biopsies using an appropriate biomarker of transformation. We describe new gene interactions through the use of a systems biology approach and we highlight some of the first studies to identify functional genes using CRISPR-Cas9 technology. We believe that this information has translational implications for the use of re-purposed existing drugs and/or new drug development. Further, we argue that the use of digital technology encompassing clinical and laboratory-based data will create relevant datasets for machine learning/artificial intelligence. We believe that therapeutic intervention at an early molecular premalignant stage should be an important preventative strategy to inhibit the development of oral squamous cell carcinoma and that this approach is applicable to other aerodigestive tract cancers. Highlights: Oral epithelial tumour progression is influenced by tumour heterogeneity, the spectrum of driver mutations and gene transcription. Driver mutations in OPMD can be used to predict malignant transformation. OPMD can be monitored dynamically using liquid biopsies and the loss of cellular senescence as a biomarker of transformation. An interactome of genes with driver mutations is reported for the first time. The identification of functional genes using CRISPR/Cas9 has translational implications.